Co. Aytch : a side show of the big show - Watkins, Samuel R. (New York, NY : Simon & Schuster, 1997)
A Confederate memoir of the Civil War.
First published in 1882 under title: 1861 vs. 1882.
"A Touchstone book."
Includes index.
Keywords: United States -- History -- Civil War, 1861-1865 -- Regimental histories; Confederate States of America. -- Army. -- Tennessee Infantry Regiment, 1st. -- Company H; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate